The Maidens [compact disc, unabridged] - Michaelides, Alex, 1977- (Macmillan Audio, 2021)
Edward Fosca is a murderer. Of this Mariana is certain. But Fosca is untouchable. Nevertheless, Mariana is determined to stop this killer, even if it costs her everything--including her own life.